INSILICO DOCKING ANALYSIS OF KAEMPHEROL AND LUTEOLIN AGAINST DIABETIC DRUG TARGET PEPCK1 - AMALORPAVAM J; DR. G. A. I. EBENEZER (International Journal of Pharma and Bio Sciences, 2014)
The fast and electronic gadgetic, lifestyle have led mankind to a complicated mesh leading to many diseases that passively spreads into the population producing an unhealthy society. Diabetes is one such disease that is gaining ground due to eating habits and sedentary lifesyte. Even though there are many pharmaceutical products available many patients prefer to revert back to the slow healthy approach integrated with natural therapeutics. In recent years, the demands on drug discovery process have increased dramatically, partly because of the necessity to recognize novel target that are both pertinent to disease and chemically tractable. The emergence of bioinformatics gives room to investigate diseases at the molecular level using computational techniques. In this study, some of the flavonoids present in the tamarind seed coat is used in the insilico docking analysis against phosphoenolpyruvate carboxykinase (PEPCK1). The phytochemical investigation of the methanolic extract of the tamarind seed coat was positive for Kaempherol and luteolin. These two flavonoids were selected for the insilico docking analysis against the target protein PEPCK1. The aim of the present study is to describe antidiabetic role of kaempherol and lately against PEPCK1.